Exopolysaccharide (EPS) synthesis by Oenococcus oeni: from genes to phenotypes. - Maria Dimopoulou; Marlène Vuillemin; Hugo Campbell-Sills; Patrick M Lucas; Patricia Ballestra; Cécile Miot-Sertier; Marion Favier; Joana Coulon; Virginie Moine; Thierry Doco; Maryline Roques; Pascale Williams; et al. (PLoS ONE, 2014)
Oenococcus oeni is the bacterial species which drives malolactic fermentation in wine. The analysis of 50 genomic sequences of O. oeni (14 already available and 36 newly sequenced ones) provided an inventory of the genes potentially involved in exopolysaccharide (EPS) biosynthesis. The loci identified are: two gene clusters named eps1 and eps2, three isolated glycoside-hydrolase genes named dsrO, dsrV and levO, and three isolated glycosyltransferase genes named gtf, it3, it4. The isolated genes were present or absent depending on the strain and the eps gene clusters composition diverged from one strain to another. The soluble and capsular EPS production capacity of several strains was examined after growth in different culture media and the EPS structure was determined. Genotype to phenotype correlations showed that several EPS biosynthetic pathways were active and complementary in O. oeni. Can be distinguished: (i) a Wzy-dependent synthetic pathway, allowing the production of heteropolysaccharides made of glucose, galactose and rhamnose, mainly in a capsular form, (ii) a glucan synthase pathway (Gtf), involved in β-glucan synthesis in a free and a cell-associated form, giving a ropy phenotype to growth media and (iii) homopolysaccharide synthesis from sucrose (α-glucan or β-fructan) by glycoside-hydrolases of the GH70 and GH68 families. The eps gene distribution on the phylogenetic tree was examined. Fifty out of 50 studied genomes possessed several genes dedicated to EPS metabolism. This suggests that these polymers are important for the adaptation of O. oeni to its specific ecological niche, wine and possibly contribute to the technological performance of malolactic starters.